PENGARUH KOMPOSISI MEDIA TANAM DAN DOSIS PUPUK KASCING TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMATVARIETAS INTAN (Solanum lycopersicum L.) - Krisnawati, Susi; Darini, Maria Theresia; Darnawi, Darnawi (Universitas Sarjanawiyata Tamansiswa, 2018)
This research aims to know the effect of grew media composition and vermicompost dosage application on the growth and yield of tomato. The reseach was conducted in Agriculture Faculty greenhouse of Sarjanawiyata Tamansiswa University, located in Tuntungan UH III Umbulharjo sub-district, Yogyakarta. According to the government of Yogyakarta, the region has an average of altitude is 114 meters above sea level and included of lowland with slope Â± 1 degrees, average of rainfall 2.012 mm/year, average of temperature is 27,2 oC, average of humidity is 24,7% Rh, and than average of light intensity is 1.833 kal/cm2/day. This reaserch was conducted in Meiâ€”Juli 2017, with use factorial 3 x 3 and one control, a complete arranged randomized design. The first factor was grew media composition consisted of three composition, namely are 1 sand : 1 soil ; 1 sand : 2 soil and 1 sand : 3 soil. The second factor was dosage of vermicompost consisted three levels are 50 g, 100 g and 150 g per polybag. Each treatment was repeated three replication with taking three plant of sample plant for each polybag. Variables observerd were plant height, age of flowers, flowers number, age of fruits, fruits number, fruits diameter, fruits weight, leaf number, leaf area, fresh weight of plant, fresh weight of root, dry weight of plant and age of harvest. The analysis showed that there was interaction effect between the two factor on variables are leaf number, fresh weight of root and dry weight of plant. Variabel of leaf number showed interaction is with grew composition 1 sand : 1 soil and vermicompost dosage is 100 gives the highets result and than variables fresh weight of root and dry weight of plant showed interaction are with grew composition 1 sand : 1 soil and vermocompost dosage is 50 g gives the highets result